Culturally and Linguistically Informed Neuropsychological Evaluation Protocol for Primarily Spanish-Speaking Adults. (29th March 2023) - Strutt, Adriana M; Armendariz, Victoria; Arias, Franchesca; Diaz Santos, Ana L; Zink, Davor; Vuong, Kevin Dat; Rossetti, Maria Agustina
Abstract: Objective: The Latina(o)/Hispanic (L/H) population represents the largest and fastest-growing ethnic group in the United States. Migration patterns have evolved and greater diversity (i.e., country of origin) is evident, highlighting the ever-changing heterogeneity of this community and the need for the field of neuropsychology to ensure equitable care for linguistically and culturally diverse communities. This paper aims to provide a flexible protocol of neuropsychological instruments appropriate for primarily Spanish-speaking adults residing in the United States. Method: Spanish measures were selected based on availability, translations/cultural modifications, accompanying normative data sets, and clinician experience/acumen. Bilingual/bicultural providers of neuropsychological services to Spanish speakers across the training spectrum working at U.S.-based medical centers implemented a multimodal approach (i.e., literature search, clinical practice parameters, and focus groups) in the development of a multi-domain primary protocol that includes core and supplemental measures that are appropriate for individuals with varying linguistic proficiency and sociocultural demographic characteristics. Results: A multi-domain, evidence-based, flexible neuropsychological protocol is presented. Recommendations for test selection based on sociocultural demographic factors and examples of clinical assessment practices are provided via a case illustration. Most instruments included may be applied across cultural and regional backgrounds. Conclusion: Provision of neuropsychological services to primarily Spanish-speaking adults presents unique challenges. Existing Spanish measures and accompanying data rarely capture the heterogeneity of L/H individuals. Although Spanish has the largest number of neurocognitive instruments, relative to other languages, robust and representative norms continue to be scarce. Future studies should prioritize collecting normative data from educationally and geographically diverse samples.